Progress of laser-induced breakdown spectroscopy in nuclear industry applications. (21st October 2019) - Wu, Jian; Qiu, Yan; Li, Xingwen; Yu, Han; Zhang, Zhi; Qiu, Aici
Abstract: In order to ensure the safety and economy of nuclear industry production, the analysis of nuclear materials and other materials used in nuclear industry environments are usually required before and during their installation and utilization, and after service. The advantages of laser-induced breakdown spectroscopy (LIBS), such as sample preparation not being required and in situ remote analysis, make it an efficient method for the analysis of hazardous samples and samples in remotely accessible or hazardous environments. The nuclear industry has become one of the fast-growing fields of LIBS application. In this review, the feasibility of LIBS in the nuclear industry is summarized from the aspects of the physical fundamentals of plasma, instrumentation, spectral analysis, and application progress. The radiation characteristics of LIBS and spectral lines of interest are discussed, along with the main influencing factors and spectral enhancement methods. LIBS instruments and spectral analysis methods used for identification are then presented, and qualitative and quantitative analysis. The various applications of LIBS in the nuclear industry and in fusion facilities are described, including the analysis of nuclear materials, isotopes, and steels and alloys. Finally, the challenges currently being encountered by LIBS applications and its potential development direction are considered.